Thermal behavior and pyrolytic degradation kinetics of polymeric mixtures from waste packaging plastics - R. Tuffi; S. D'Abramo; L. M. Cafiero; E. Trinca; S. Vecchio Ciprioti (eXPRESS Polymer Letters)
The thermal behavior and pyrolytic kinetic analysis of main waste polymers (polypropylene (PP), polyethylene film (PE), poly(ethylene terephthalate) (PET), polystyrene (PS)) and three synthetic mixtures representing commingled postconsumer plastics wastes (CPCPWs) output from material recovery facilities were studied. Thermogravimetry (TG) pyrolysis experiments revealed that the thermal degradation of single polymers and the synthetic mixture enriched in PP occurred in one single step. The other two mixtures underwent a two-consecutive, partially overlapping degradation steps, whose peaks related to the first-order derivative of TG were deconvoluted into two distinct processes. Further TG experiments carried out on binary mixtures (PS/PP, PET/PP, PET/PEfilm and PP/PEfilm) showed a thermal degradation reliance on composition, structure and temperatures of single polymer components. A kinetic analysis was made for each step using the Kissinger-Akahira-Sunose (KAS) method, thus determining almost constant activation energy (Ea) for pyrolysis of PS, PET, PP and PE film in the range 0.25<α<0.85, unlike for pyrolysis of CPCPWs, with particular reference to CPCPW1 and the second step of CPCPW2 and CPCPW3, both ascribable to degradation of PP and PE film. To account for the reliability of these values the integral isoconversional modified method developed by Vyazovkin was also applied.